Testing Novel Inactivation Methods and Adjuvants for Vaccines Against Streptococcus agalactiae in Nile Tilapia Oreochromis niloticus - Ramos-Espinoza, Fernando Carlos [UNESP]; Cueva-Quiroz, Victor Alexander [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Alvarez-Rubio, Norquis Caled [UNESP]; de Mello, Nicoli Paganoti [UNESP]; de Moraes, Julieta Rodini Engrácia [UNESP] (Springer Nature, 2022)
Inactivation by hydrogen peroxide and pH manipulation are two novel methods used recently in experimental vaccines against Streptococcus agalactiae in Nile tilapia. Here we describe in detail inactivation using novel methods as well as the classical method of inactivation. These vaccines showed similar moderate efficacy when compared to the conventional formaldehyde vaccine. In addition, we describe the inclusion of adjuvants in a hydrogen peroxide vaccine.
Keywords: Aluminum hydroxide; Bacterial inactivation; Hydrogen peroxide; Streptococcosis; Vaccination